The Symptomatic Improvement of Metastatic Brain Tumor Patients Based on Clinical and Distress Thermometer in Adjunctive Psychotherapy - Tiara Aninditha; Dian Oktaria Safitri; Henry Riyanto Sofyan; Sylvia Detri Elvira; Irmia Kusumadewi; Feranindhya Agiananda (Indonesian Journal of Cancer, 2023)
Background: Along with the increasing incidence of primary cancer, metastatic brain tumors are becoming more common. Metastatic brain tumor patients go through a great deal of distress. Therefore, providing adequate standard therapy can alleviate patients’ clinical symptoms and improve their overall quality of life. This study aimed to investigate the role of symptomatic treatments and adjunctive psychotherapy in patients with metastatic brain tumors. Methods: We conducted a randomized, single-blind, parallel design without matching and pragmatic clinical trial at Cipto Mangunkusumo Hospital from August 2019 – June 2020. A total of 30 metastatic brain tumor patients were divided into 2 groups: (1) The treatment group which received a combination of symptomatic and adjunctive psychotherapy, and (2) The control group which was given symptomatic therapy only. The patients’ distress level was evaluated using a distress thermometer (DT). Data analysis was carried out using the Chi-square test, Fisher exact’s, and binominal test.Results: All patients in the treatment group experienced a significant improvement in overall DT scores before and after adjunctive psychotherapy (p=0.01). Symptomatic therapy alleviates headaches and seizures significantly by 100% with or without psychotherapy. Conclusions: The standard symptomatic treatment of metastatic brain tumors can alleviate clinical symptoms in both groups, especially for headaches and seizures. An adjunctive psychotherapy may significantly improve the overall DT.